ANALISIS KESENJANGAN HARAPAN ANTARA NASABAH DAN MANAJEMEN TERHADAP PENYAMPAIAN INFORMASI KEUANGAN (ROA, ROE, CAR) DAN NON KEUANGAN(PELAYANAN, PRINSIP SYARIAH, BIAYA PELAYANAN) BANK SYARIAH (Studi Empiris Bank Syariah di Semarang) - Sudarmaji, Heri (STIE Totalwin Semarang, 2011)
The use of revenue sharing between depositors mudharabah saving and the bank in the operation of Islamic Banks, has created an agency problem. Regarding with this problem, Banks should provide both financial and non financial information for the depositors mudharabah saving. This research tests again there is gap in the information provided by banks as the provider of information to the depositors as the user of the information. Based on asymmetry information theory, depositors as a party with less information, would demand more information to the banks. However for some reasons, banks might restrict the information provided to the depositors mudharabah saving One hundred seventy-five customers consists of mudharabah saving account customer, mudharabah investment account customer, wadiah current account customer and financing customer and ninety seven staffs of Islamic banks in Semarang using technical convenience sampling have been surveyed with questionnaire. This research used independent sample t-test in analyzing the expectation gap of the two groups. The result shows that in general, there is no expectation gap between overall customers and Islamic Banks Managers in both financial and non financial disclosure. But there exists expectation gap between mudharabah investment account customer and Islamic Bank Managers in financial and non financial disclosure